Urgency of Mathematics Learning in Preparing Cognitive Competence of Santri (Case Study at Misykatul Atsar Islamic Boarding School in Salatiga) - Chayatun Ni'mah (Hipotenusa : Journal of Mathematical Society, 2020)
The purpose of this study was to determine the urgency of learning mathematics in preparing the cognitive competencies of students of the Islamic Boarding School. This research uses a field approach with descriptive qualitative methods. The research subjects were administrators, caregivers, mathematical teachers, as well as students in the Misykatul Atsar Islamic boarding school. With observation, interview, and documentation techniques. The results of the study show that: (1) the urgency of mathematics learning at the Islamic boarding school Misykatul Atsar said it was important for the following reasons: first, mathematics as a language for understanding science. Second, mathematics is used to solve problems. Third, mathematics is implemented as a religious lesson in the cottage. Fourth, mathematics is the provision when Santri has left the hut. (2) How to prepare the cognitive competencies of the Santri  Misykatul Atsar boarding school. First, the Teacher's Way: giving a prolog in delivering learning material using language that is easily understood by students. During the learning process by explaining in front of the class the material being presented and giving examples of questions then the discussion about the material that was submitted earlier with questions and answers after clearly given the practice questions. Second, how to caregivers and administrators: bring math teachers to the cottage to teach mathematics once a week and often give him practice. Then ask students to repeat the material with friends, work on sample problems, get used to counting, and be interested when learning mathematics.